2012
DOI: 10.1149/2.052211jes
|View full text |Cite
|
Sign up to set email alerts
|

LiNi0.4Mn1.6O4/Electrolyte and Carbon Black/Electrolyte High Voltage Interfaces: To Evidence the Chemical and Electronic Contributions of the Solvent on the Cathode-Electrolyte Interface Formation

Abstract: Solvent and lithium salt decomposition products on LiNi x Mn y O 4 -type electrodes are known to be ROM, ROCO 2 M (M = Li, Ni, Mn), LiF, Li x PF y O z , polycarbonates and polyethers. These compounds are chemically formed due to the high nucleophilic character of spinel oxide and LiPF 6 decomposition. The high potentials (> 4.7 V vs. Li/Li + ) may cause EC and PC polymerization, while DMC forms oligomers. The use of carbon black-based electrodes highlights electronic and, surprisingly, chemical contributions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 15 publications
2
54
0
Order By: Relevance
“…In order to show that an LiPAA film acts as a physical barrier that can passivate high‐voltage cathodes, cyclic voltammetry (CV) studies were conducted with working electrodes consisting of CB + binders on Al foils. The reactivity of most of the relevant electrolyte solutions on CB particles at high voltages (e.g., >4.5 V vs Li) has been clearly demonstrated in recent studies, and is believed to exacerbate the CEI instability issues surrounding the use of high‐voltage cathodes. In Figure h,i, irreversible oxidation occurs for Al/CB + PVdF electrodes, which becomes more prominent at high voltages (>4.5 V vs Li) and at an elevated temperature of 45 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to show that an LiPAA film acts as a physical barrier that can passivate high‐voltage cathodes, cyclic voltammetry (CV) studies were conducted with working electrodes consisting of CB + binders on Al foils. The reactivity of most of the relevant electrolyte solutions on CB particles at high voltages (e.g., >4.5 V vs Li) has been clearly demonstrated in recent studies, and is believed to exacerbate the CEI instability issues surrounding the use of high‐voltage cathodes. In Figure h,i, irreversible oxidation occurs for Al/CB + PVdF electrodes, which becomes more prominent at high voltages (>4.5 V vs Li) and at an elevated temperature of 45 °C.…”
Section: Resultsmentioning
confidence: 99%
“…We recently explored the capacity fading of such full cells and demonstrated how side reactions at the cathode side badly affect the passivation of the graphite anode, which in turn leads to a loss of active Li ions in the cells . Carbon black (CB) particles, a necessary conducting component in all composite cathodes for Li batteries, have been shown to be particularly reactive under high‐voltage conditions, acting as a catalyst for electrolyte solution oxidation . Due to the mandatory presence of CB and the imperfect passivation of composite LNMO cathodes, undesirable reactions occur at the CEI.…”
Section: Introductionmentioning
confidence: 99%
“…Xu , has discussed the oxidation and degradation of conventional carbonate-based electrolytes in detail. With the existence of LiPF 6 or LiBF 4 in carbonate-based electrolyte, it has been reported that the CEI is composed of inorganic species such as LiF, ROM, ROCO 2 M (R is organic group, M = Li, Ni, Mn), Li x PF y O z or Li x BF y O z as well as organic species such as polyethers and polycarbonates. Though the polymeric CEI film resulting from the oxidation of ethylene carbonate (EC) or propylene carbonate (PC) may stabilize the interface during subsequent cycling, its protective function is still doubted due to the incomplete coverage on cathode surfaces. , To understand better the degradation mechanisms of electrolyte, Dedryvere et al studied the interface reaction process between LiNi 0.4 Mn 1.6 O 4 and EC/PC/dimethyl carbonate (DMC) electrolyte by chemical sensitive X-ray photoelectron spectroscopy (XPS) and electrochemical sensitive EIS techniques. They found that the electroadsorption mechanism was predominant at the first cycle whereas the film-formation mechanism caused by electrolyte decomposition became predominant during subsequent cycling.…”
Section: Surface and Interface Chemistrymentioning
confidence: 99%
“…It was worth noticing that the E a value was calculated to be 1 kJ mol –1 , a value lower than that of traditional gel electrolyte (10 kJ mol –1 ) and solid electrolyte (40 kJ mol –1 ). ,, A conductivity value of 6.79 × 10 –4 S cm –1 was achieved at room temperature, which was attributed to the low energy barrier . The high ionic conductivity value may result from the soft segments of PMMA and the plasticization of carbonate solvent and the relevant impedance spectra at different temperature were depicted in Figure S4.…”
Section: Resultsmentioning
confidence: 97%